NLRP1-Mediated Antidepressant Effect of Ketamine in Chronic Unpredictable Mild Stress Model in Rats - Aricioğlu, Feyza (Psychiatry Investig, 2020)
OBJECTIVE: NOD-like receptor protein 1 (NLRP1) inflammasome complex has been recently associated with chronic unpredictable mild stress (CUMS) model of depression. Our aim was to investigate whether ketamine-induced antidepressant effect is associated with suppression of NLRP1. METHODS: Wistar albino rats were divided into control, CUMS, CUMS+acute ketamine (a single 10 mg/kg dose) and CUMS+chronic ketamine (daily 10 mg/kg injections for 3 weeks) groups (n=10 for each group). Sucrose preference test and forced swimming test were performed to assess anhedonia and immobility time respectively for the severety of depression symptoms. Brain tissues were dissected and prefrontal cortex and hippocampus regions were used for real-time polymerase chain reaction (PCR) and immunohistochemical analysis. RESULTS: CUMS procedure significantly induced depressive-like symptoms whereas both acute and chronic ketamine treatment ameliorated them. mRNA expression levels of NLRP1, caspase 1, apoptosis-associated speck-like protein containing a CARD (ASC), NF-κB, endothelial nitric oxide synthase, IL-1β, IL-6, toll-like receptor 4 (TLR-4) and purinergic 2×7 receptor (P2X7R) and numbers of Iba- 1+and GFAP+glial cells were reduced by acute and/or chronic ketamine treatment. CONCLUSION: In the present study for the first time upstream and downstream elements of the NLRP1 inflammasome complex are shown to be suppressed by ketamine thus reinforcing the involvement of NLRP1 in the physiopathology of depression.